2010
DOI: 10.1088/0953-2048/23/8/083001
|View full text |Cite
|
Sign up to set email alerts
|

Unified scaling law for flux pinning in practical superconductors: I. Separability postulate, raw scaling data and parameterization at moderate strains

Abstract: The unified strain-and-temperature scaling law underlies the many pinning-force-model expressions proposed to parameterize the dependence of the critical current I c on magnetic field B, temperature T and applied axial strain ε in superconductors for high-field magnet design. Increasingly, these expressions have been evaluated by use of multiparameter simultaneous fits, without the use of scaling. In this review, we reintroduce the unified scaling law on which the recent parameterizations are based, as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(91 citation statements)
references
References 67 publications
3
88
0
Order By: Relevance
“…The retention of the same , with temperature scaling, if it applies, shows that temperature is not altering any important relative length scales, or pinning potentials that determine the shape of F(b). In contrast it is known that changes in microstructure will alter the fitting parameters , for some superconductors [1,20] and between different superconductors there are considerable variations.…”
Section: Magnetic Field Constraintsmentioning
confidence: 98%
See 2 more Smart Citations
“…The retention of the same , with temperature scaling, if it applies, shows that temperature is not altering any important relative length scales, or pinning potentials that determine the shape of F(b). In contrast it is known that changes in microstructure will alter the fitting parameters , for some superconductors [1,20] and between different superconductors there are considerable variations.…”
Section: Magnetic Field Constraintsmentioning
confidence: 98%
“…Various explanations have been offered for this, but without consensus. The same shape implies that data over multiple conditions can be scaled to a common curve, a useful property for constructing empirical models used in engineering of devices [20].…”
Section: Magnetic Field Dependence Of J Cmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed analysis of F p (H) in terms of the size, spacing and nature of the pinning centers, and the nature of their interaction with the flux lines has been done by Dew-Hughes [27], and we have presented a similar analysis in a recent work [21]. To investigate into the flux line pinning mechanisms in the present alloys using DewHughes model, we have used a normalized field h, where h ¼ l 0 H l 0 H Ã , H ⁄ being the field at which the (approximately) linearly falling portion of the F p versus l 0 H curves (in the higher H side) extrapolate to F p = 0 [24,28]. We have found that the F p ðhÞ curves for the present alloys cannot be fitted by any of the functions of form F p 1h p ð1 À hÞ q , where the values of p and q depend on the details of the pinning mechanism, as prescribed by Dew-Hughes [24,27].…”
Section: Alloy Compositionsmentioning
confidence: 99%
“…This wire has had low anisotropy in a range from 3 to 5%. The scaled pinning force on magnetic field of our Cu shield wires determines dominant of pinning mechanism as the grain boundary mechanism [9,10]. The evaluated from scaling process parameter p is close to 0.5 and appropriate q parameter is almost equal to 2 -all suggested the dominant grains boundary pinning (Fig.…”
Section: Resultsmentioning
confidence: 76%